Competition and Efficiency in Banking : Behavioral Evidence from Ghana - Mathisen, Johan; Buchs, Thierry (Washington, D.C. : International Monetary Fund, 2005)
This paper assesses the degree of bank competition and discusses efficiency with regard to banks' financial intermediation in Ghana. By applying panel data to variables derived from a theoretical model, we find evidence for a noncompetitive market structure in the Ghanaian banking system, which may be hampering financial intermediation. We argue that the structure, as well as the other market characteristics, constitutes an indirect barrier to entry thereby shielding the large profits in the Ghanaian banking system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet